Comparison of vocal exercises on vaccai, concone and marchesi / Kamissantirafika Mohamad Alib - Mohamad Alib, Kamissantirafika (2012)
Vocal warm up exercises are incredibly important to a healthy singing voice as they help to basically for vocal production which is ranging from the physiological process to the artistic aspects. Developing a warm up routine can benefit us for more than physical reasons; by taking the time to connect to our voice and prepare, we will set ourself up mentally for a great performance, practice, or recording session (Frederick, T. 2008).